2018
DOI: 10.3389/fmicb.2018.00086
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in Mitochondrial Group I Introns among Cryptococcus neoformans and Cryptococcus gattii Genotypes and Its Association with Drug Susceptibility

Abstract: Cryptococcosis, one of the most important systemic mycosis in the world, is caused by different genotypes of Cryptococcus neoformans and Cryptococcus gattii, which differ in their ecology, epidemiology, and antifungal susceptibility. Therefore, the search for new molecular markers for genotyping, pathogenicity and drug susceptibility is necessary. Group I introns fulfill the requisites for such task because (i) they are polymorphic sequences; (ii) their self-splicing is inhibited by some drugs; and (iii) their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 65 publications
3
25
1
Order By: Relevance
“…In general, the number and classes of introns were highly dynamic changes in the Polyporales species, which proved that numerous intron loss or gain events occurred in the evolution of Polyporales . The result was consistent with previous studies that the fungal group I introns appears to result from numerous losses and gains of the mobile genetic elements 40 , 43 , 66 , 67 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, the number and classes of introns were highly dynamic changes in the Polyporales species, which proved that numerous intron loss or gain events occurred in the evolution of Polyporales . The result was consistent with previous studies that the fungal group I introns appears to result from numerous losses and gains of the mobile genetic elements 40 , 43 , 66 , 67 .…”
Section: Discussionsupporting
confidence: 93%
“…In general, the number and classes of introns were highly dynamic changes in the Polyporales species, which proved that numerous intron loss www.nature.com/scientificreports/ or gain events occurred in the evolution of Polyporales. The result was consistent with previous studies that the fungal group I introns appears to result from numerous losses and gains of the mobile genetic elements 40,43,66,67 . The arrangement of mitochondrial genes can also serve as an important reference for revealing phylogenetic relationships among species [68][69][70] .…”
Section: Discussionsupporting
confidence: 93%
“…The cox1 gene of C. fumosa contained the largest number of introns among the 22 Agaricales species, while four novel Pcls were detected in the cox1 gene of C. fumosa . Intron considered as an important genetic element in the mitogenome of fungi (Burke 1988 ; Gomes et al 2018 ), and its dynamic changes can significantly affect the organization and size of the mitogenome of fungi (Hamari et al 2002 ; Himmelstrand et al 2014 ). The origin and evolution of the novel Pcls needed to be further analyzed to understand the evolution of the C. fumosa mitogenome.…”
Section: Discussionmentioning
confidence: 99%
“…A species-specific pattern of intron distribution has been also observed in F. oxysporum [188] and Fusarium fujikuroi species complex (FFSC) [212]. Recently, Gomes et al (2018) [213] suggested that group I introns are promising targets for developing novel tools for fungicide susceptibility. Some fungicides inhibit self-splicing of group I introns, which is indispensable for pathogen survival under parasitic conditions [213].…”
Section: Perspectives Of Targeting Mtdna For Barcoding Of Plant Pathomentioning
confidence: 96%
“…Recently, Gomes et al (2018) [213] suggested that group I introns are promising targets for developing novel tools for fungicide susceptibility. Some fungicides inhibit self-splicing of group I introns, which is indispensable for pathogen survival under parasitic conditions [213]. Intron distribution has been suggested as an important contributor to the virulence and drug tolerance of human fungal pathogens Cryptococcus neoformans and Cryptococcus gattii.…”
Section: Perspectives Of Targeting Mtdna For Barcoding Of Plant Pathomentioning
confidence: 99%